Pemodelan dan simulasi kinetika reaksi alkoholisis minyak Jarak pagar (Jatropha curcas) dengan katalisator zirkonia tersulfatasi - Heri Rustamaji; Hary Sulistyo; Arief Budiman (Jurnal Rekayasa Proses, 2010)
Jatropha oil is a very potential source of biodiesel fuel that can be processed through alcoholysis. In the present work, a study on alcoholysis of Jatropha oil with the use of solid acid catalyst was conducted in a wellmixed batch reactor. The study involved varying reaction temperatures of 100°C to 140°C, ethanol-oil molar ratio of 9, agitation speed of 1000 rpm and catalyst loading of 3% with respect to the oil. The reaction was carried out for 120 minutes; meanwhile samples were taken from the reactor every 15 minutes for glycerol analysis. In order to predict kinetics parameter of the alcoholysis reaction, a mathematical model of consecutive reactions was developed. The Matlab software was used to solve the simultaneous differential equations. Over the range of variables used in the experiment, the mathematical model was able to fit the experimental data quite well. The calculation results showed that the values of collision frequency factor for the consecutive reactions are 5.13 x 103; 5.682 x 103, and 2.534 x 103 (cm3/mgek) (cm3/g.cat/min). Meanwhile, the activation energies for the consecutive reaction are 4,176; 4,310 and 6,019 cal/mol.